2020
DOI: 10.1177/1556984520930070
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage Versus Sequential Hybrid Radiofrequency Ablation: An In Vitro Evaluation

Abstract: Objective To compare lesion size and depth between a 1-step, a sequential, and a delayed radio-frequency ablation in a hybrid setup. Methods Left atrium tissues obtained from fresh porcine hearts were mounted into the ABLABOX simulator. Based on the time differences between the index epicardial (epi) and consequent endocardial (endo) ablation, 3 study groups were compared: a 1-stage (SEQ- 0) group (0-minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… 23 , 24 Indeed, in a pre-clinical model from our group, simultaneous epi–endo ablation produced broader and deeper lesions. 25 Two-stages hybrid AF ablation might be associated with shorter procedural time and the possibility to assess lesions after oedema resolution.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Indeed, in a pre-clinical model from our group, simultaneous epi–endo ablation produced broader and deeper lesions. 25 Two-stages hybrid AF ablation might be associated with shorter procedural time and the possibility to assess lesions after oedema resolution.…”
Section: Discussionmentioning
confidence: 99%
“…29 Nonetheless, the time-frame between the endocardial and the epicardial steps can vary from a few hours up to 6 months, [30][31][32][33][34][35][36] and some groups perform either onestage or staged procedures. [37][38][39] In our previous experience, 40 we failed to find any difference in lesion depth between single-stage or endocardial procedures performed after a 60-minute delay or after a 240-minute delay. Notably, overall, no transmural lesion was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the time-frame between the endocardial and the epicardial steps can vary from a few hours up to 6 months [30][31][32][33][34][35][36] , and some groups perform either one-stage or staged procedures [37][38][39] . In our previous expe-rience 40 , we failed to find any difference in lesion depth between 1-stage or endocardial procedures performed after a 60-minute delay or after a 240-minute delay. Notably, overall, no transmural lesion was obtained.…”
Section: Discussionmentioning
confidence: 62%
“…However, to date, the superiority of the hybrid procedure over catheter ablation is still reason for debate, and available data come from small case series with variable lesion sets and devices used 43 . Even more rarely published studies have demonstrated the superiority of the hybrid procedure with surgical ablation 40,44 . Nonetheless, encouraging results in terms of being arrhythmia-free and having a reduction of reintervention rates make this technique very promising 40,45 .…”
Section: Hybrid Ablationmentioning
confidence: 99%
See 1 more Smart Citation